Pengaruh Pelaksanaan Program Usaha Kesehatan Gigi Sekolah Terhadap Kejadian Karies Pada Anak Di SD Inpres 5 Birobuli - utariii; Arsad; Yulistina; Rezki Dirman; Yusnita (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Dental and oral health is an important part of children's health, especially at school age which is the early period of forming healthy living habits. The School Dental Health Business Program (UKGS) was developed as a promotive and preventive effort to instill dental health maintenance behaviors from an early age. However, the effectiveness of its implementation often differs from school to school. This study aims to analyze the effect of the implementation of UKGS on the incidence of caries in students at SD Inpres 5 Birobuli, Palu City, Central Sulawesi Province. The research uses a quantitative method with a cross-sectional design. From a total population of 456 students, as many as 103 students in grades I and II were selected as samples. Data were obtained through questionnaires and dental examinations, then analyzed using the Chi-square test (α=0.05). From this study, the results were obtained that the implementation of UKGS in the school is still very low (less than 25%). Of the 103 children, 73 (70.9%) had caries. The statistical test obtained a p-value of 0.477, which indicates that there is no significant influence between the implementation of UKGS and the incidence of caries in students. Thus, it is necessary to strengthen the implementation of UKGS at SD Inpres 5 Birobuli in order to play a more effective role in reducing dental caries in school children. Increasing educational activities and improving the implementation of dental health business programs is recommended to support better dental and oral health outcomes